Actinobacillus pleuropneumoniae Interaction With Swine Endothelial Cells - Plasencia-Muñoz, Berenice; Avelar-González, Francisco J.; De la Garza, Mireya; Jacques, Mario; Moreno-Flores, Adriana; Guerrero-Barrera, Alma L. (Frontiers in Veterinary Science, 2020)
Actinobacillus pleuropneumonia is an exclusive swine respiratory tract pathogen and the etiological agent of swine pleuropneumonia which affects pigs of all ages and has high rates of morbidity and mortality which generates large economic losses for the pig industry. It is a widely studied bacterium, however its pathogenesis is not yet fully understood. The prevalence of the 18 serotypes of A. pleuropneumoniae varies by geographic region, with serotypes 1, 3, 5b and 7 being the most prevalent in North America and more specifically in Mexico. Actinobacillus pleuropneumoniae is described as a strict extracellular pathogen with tropism for lower respiratory tract. However, this study describes the ability of these serotypes to adhere to non-phagocytic cells, using as cell model endothelial cells which are in close contact with alveolar cells in respiratory tract, as well as their ability to invade them, indicating that it is both an extra and intracellular pathogen.